Cost and Benefits of Implementing Trade Facilitation Measures under Negotiations at the WTO: an Exploratory Survey - Yann Duval (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
This study suggests that the WTO may need to establish a long-term institutional mechanism to deal with evolving trade facilitation measures and issues. Countries may also agree on a subset of well-defined TFMs to be implemented by all, as well as on a complementary list of possibly more controversial TFMs from which countries would select, based on their own needs and specificity, a pre-determined number of measures for implementation.
Keywords: F1; 330; WTO; Trade Facilitation